Composite structure for pressure sensor and pressure sensor - Patents.com
The composite structure for pressure sensors, with a flexible conductive graphene coating on elastomeric microstructures, addresses the irregularity of existing sensors, achieving high sensitivity, low hysteresis, and independence from strain rate and temperature.
Patent Information
- Application Number
- JP2021573505
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-10
- Filing Date
- 2020-06-10
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2040-06-10
AI Technical Summary
Existing pressure sensors with hierarchically structured graphite and PDMS composite materials have irregular porous microstructures, making it difficult to adjust their performance for special applications.
A composite structure for pressure sensors is developed, featuring an array of microstructures made from elastomeric material with a flexible conductive coating. The coating, which includes graphene, has a Young's modulus higher than the elastomeric material, maintaining the surface morphology and reducing viscoelastic effects.
The sensor achieves high sensitivity, a wide sensitivity range, low hysteresis, and is independent of strain rate and temperature, with the ability to detect small pressures and high-frequency signals, ensuring reliable performance over countless cycles.
Smart Images

Figure 0007663516000002 
Figure 0007663516000003 
Figure 0007663516000004
Abstract
Description
[Technical field]
[0001] The present invention relates generally to composite structures for pressure sensors, pressure sensors, methods of sensing pressure using pressure sensors, and methods of manufacturing composite structures for pressure sensors. [Background technology]
[0002] Any mention and / or discussion of prior art throughout this specification should not be considered in any way as an admission that this prior art is well known in the art or forms part of the common general knowledge.
[0003] Sun et al. utilized graphene and polydimethylsiloxane (PDMS) to create a hierarchically structured sensor (see Non-Patent Document 1). Graphite was first mixed with PDMS and cubic sodium chloride (NaCl). After washing away the NaCl, a porous composite film was obtained. By using sandpaper as a mold, the surface morphology of this composite material can also be microstructured. The developed sensor can be used to detect pressure based on the piezoresistive working principle, which is common to many tactile sensors and generally measures the change in resistance when pressure is applied. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Sun, Q. et al. Fingertip-Skin-Inspired Highly Sensitive and Multifunctional Sensor with Hierarchically Structured Conductive Graphite / Polydimethylsiloxane Foams. 1808829, 1-11 (2019) [Non-Patent Document 2] BCK Tee, A. Chortos, RR Dunn, G. Schwartz, E. Eason, Z. Bao, Adv. Funct. Mater. 2014, 24, 5427 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the resulting porous microstructure is irregular with the manufacturing method described in Non-Patent Document 1, and therefore the sensor cannot be tailored to the desired performance for a specific application.
[0006] SUMMARY OF THE PRESENT EMBODIMENTS Embodiments of the present invention seek to address at least one of the above problems. [Means for solving the problem]
[0007] According to a first aspect of the present invention, there is provided a composite structure for a pressure sensor comprising an array of microstructures made from an elastomeric material and a flexible conductive coating formed on the array of microstructures, whereby a surface morphology of the array of microstructures is substantially maintained for the coated array of microstructures, the flexible conductive coating exhibiting a Young's modulus higher than that of the elastomeric material.
[0008] According to a second aspect of the present invention there is provided a pressure sensor including the composite structure of the first aspect.
[0009] According to a third aspect of the present invention, there is provided a method of manufacturing a composite structure for a pressure sensor comprising forming an array of microstructures made from an elastomeric material; and forming a flexible conductive coating formed on the array of microstructures, whereby a surface morphology of the array of microstructures is substantially maintained for the coated array of microstructures, the flexible conductive coating exhibiting a higher Young's modulus than that of the elastomeric material.
[0010] According to a fourth aspect of the present invention, there is provided a pressure sensing method using the pressure sensor of the second aspect.
[0011] Embodiments of the invention will be better understood and readily apparent to those skilled in the art from the following description, given by way of example only and in conjunction with the drawings, in which: [Brief description of the drawings]
[0012] [Figure 1a] FIG. 1 shows a schematic diagram of a process for preparing a graphene / graphene oxide layer on a nanostructured PDMS film according to an illustrative embodiment. [Figure 1b] FIG. 13 shows a schematic top view illustrating a microstructure / sensor array centered on an interdigitated electrode, according to an exemplary embodiment. [Figure 1c] FIG. 13 is a schematic cross-sectional view illustrating a microstructure / sensor array centered on an interdigitated electrode, according to an exemplary embodiment. [Figure 2a] Figure 14 Scanning electron microscope (SEM) images of as-prepared Gr-GO on polymer samples using the blade method of GO and supernatant Gr. [Figure 2b] FIG. 13 shows another SEM image of as-prepared Gr-GO on polymer sample using the blade method of GO and supernatant Gr. [Figure 2c] FIG. 13 shows another SEM image of as-prepared Gr-GO on polymer sample using the blade method of GO and supernatant Gr. [Figure 2d] FIG. 14 SEM images of the as-prepared Gr-GO on polymer sample with bottom Gr. [Figure 2e] FIG. 13 SEM image of the as-prepared Gr on polymer sample without the presence of GO layer. [Figure 2f] FIG. 13 illustrates an SEM image of as-prepared Gr-GO on polymer sample with a thin layer of GO coated by braiding in accordance with an illustrative embodiment. [Figure 2g]FIG. 14 SEM images of the as-prepared Gr-GO on polymer sample with a thick layer of GO and buckles formed by drop-casting of GO. [Figure 3a] 1 shows a graph of resistance versus pressure for a graphene sensor according to an example embodiment, with a forward and backward correspondence, and an inset graph showing sensitivity versus pressure. [Figure 3b] 1A-1D show pressure responses of graphene sensors according to various embodiments. [Figure 3c] FIG. 13 illustrates a graph showing the effect of Gr concentration on tunable pressure response in accordance with an exemplary embodiment. [Figure 4a] 1 is a graph illustrating the strain rate independence of a graphene sensor in accordance with an exemplary embodiment, where the pressure response is the same at different strain rates. [Figure 4b] 1 is a graph illustrating the temperature independence of a graphene sensor according to an exemplary embodiment. The pressure response shows little change when the temperature is increased from room temperature to 60° C. [Figure 5a] FIG. 13 illustrates a graph showing pressure response of a sensor according to an exemplary embodiment from 1st cycle to 10,000th cycle. [Figure 5b] FIG. 13 illustrates the loading and unloading behavior of a sensor according to an exemplary embodiment after 10,000 cycles, showing that hysteresis remains low. [Figure 5c] FIG. 13 illustrates continuous measurement of sensor performance of a sensor according to an exemplary embodiment over 1000 cycles. [Figure 5d] FIG. 1 illustrates the loading and unloading behavior of a graphene sensor according to an embodiment 8 weeks after fabrication. [Figure 6a] FIG. 13 is a schematic diagram showing a simulation of the equivalent surface resistance of a graphene sensor according to an exemplary embodiment of an “electrode in sensor” design. [Figure 6b] FIG. 13 is a schematic diagram illustrating a simulation of the equivalent surface resistance of a graphene sensor according to an exemplary embodiment of a “sensor in electrodes” design. [Figure 7a] FIG. 1 illustrates a schematic diagram of an equivalent circuit of a graphene sensor in accordance with an illustrative embodiment. [Figure 7b] FIG. 13 illustrates an IV curve portion of a graphene sensor according to an exemplary embodiment under an applied load of 0 kPa. [Figure 7c] FIG. 13 illustrates an IV curve portion of a graphene sensor according to an exemplary embodiment under an applied load of 13.6 kPa. [Figure 7d] FIG. 13 illustrates an IV curve portion of a graphene sensor according to an exemplary embodiment under an applied load of 26.6 kPa. [Figure 8] FIG. 2 illustrates an upper graph showing successive detection of varying small weights by a sensor according to an exemplary embodiment, and a lower graph showing successive detection of the same small weights by a sensor according to an exemplary embodiment. [Figure 9a] FIG. 1 illustrates a schematic diagram of a setup for detecting vibrations using a graphene sensor in accordance with an illustrative embodiment. [Figure 9b] 13 is a graph showing detection results using a graphene sensor according to an exemplary embodiment of dynamic external forces having frequencies of 500 Hz, 1000 Hz, and 1500 Hz. [Figure 9c] FIG. 13 is a diagram showing a Fast Fourier Transform (FFT) of the detection result using a graphene sensor according to an exemplary embodiment of a dynamic external force with a frequency of 500 Hz. [Figure 9d] FIG. 13 shows a Fast Fourier Transform (FFT) of the detection result using a graphene sensor according to an exemplary embodiment of a dynamic external force having a frequency of 1000 Hz. [Figure 9e] FIG. 13 shows a Fast Fourier Transform (FFT) of the detection result using a graphene sensor according to an exemplary embodiment of a dynamic external force having a frequency of 1500 Hz. [Figure 10] FIG. 13 shows an atomic force microscope (AFM) image of an edge of a uniform layer of Gr nanoflakes used in a composite structure, according to an example embodiment. [Figure 11]FIG. 11 illustrates a flowchart 1100 illustrating a method for manufacturing a composite structure for a pressure sensor in accordance with an illustrative embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The present invention provides a microstructured composite as a highly sensitive tactile sensor with damping viscosity in sensor performance. The excellent deformability of the microstructured soft elastomer is utilized to achieve high sensitivity and wide sensitivity range. A stiff but flexible coating layer with both high Young's modulus (e.g., more than 10 times that of elastomer microstructures) and flexibility (e.g., graphene), with a high Young's modulus up to 1 TPa, but still flexible and stretchable, is designed on the surface of the elastomer according to the exemplary embodiment to reduce the problems caused by viscoelastic effects. As a result, the sensor according to the exemplary embodiment has a wide sensing range of 140 kPa with a sensitivity of at least 10 6 Ω kPa -1 High sensitivity up to 1000 psig can be achieved. Low hysteresis, temperature and strain rate independence are also observed. The sensor according to the exemplary embodiment is reliable and can maintain consistent performance after countless cycles and over a long period of time. Based on the change in contact resistance and quantum tunneling effect, an analytical model is proposed to analyze the sensing mechanism of the sensor according to the exemplary embodiment. The sensor according to the exemplary embodiment can be applied to detect small pressure (e.g., 8 Pa) and high frequency signals (at least 1500 Hz).
[0014] Embodiments of the present invention use microstructures with more regular geometries compared to random geometries with tunable parameters, e.g., size and density of the micropyramids. Also, embodiments of the present invention use structures based on changes in contact resistance, taking advantage of the high elastic modulus (e.g., at least an order of magnitude higher than microstructures) and good flexibility of graphene (approximately 1 Tera Pascal) to achieve viscosity reduction sensor performance.
[0015] Fabrication of Microstructured PDMS Films According to Exemplary Embodiments Silicon elastomer and crosslinker were mixed in a weight ratio of 10:1, followed by vigorous mixing at a speed of 2500 rpm for 2 min. The mixture was spin-coated onto a treated non-sticky layer (e.g., "Tosyl") silicon mold patterned with a micropyramid array with customizable size and spacing of each pyramid structure. For details of the patterning method used in the exemplary embodiment, please refer to Non-Patent Document 2. The sample was then degassed in a desiccator for 30 min to remove air bubbles generated during mixing. Polyethylene terephthalate (PET) was selected as the substrate and treated with O2 plasma to make the surface hydrophilic for good adhesion with PDMS. After degassing, the plasma-treated substrate was pressed on top of the PDMS mixture on the mold and cured at 80°C for at least 4 h. Finally, the mold was peeled off, leaving the microstructured PDMS film on the substrate for further testing.
[0016] Fabrication of graphene / graphene oxide layers on microstructured PDMS films FIG. 1a shows a schematic diagram of a process for preparing a graphene / graphene oxide layer on a nanostructured PDMS film according to an exemplary embodiment.
[0017] Specifically, FIG. 1a provides a schematic diagram for sample preparation according to an exemplary embodiment. Graphene oxide (GO) can be easily dispersed in water (e.g., 10 mg / ml) by ultrasonication for 1 h, as shown at 100, and the quality of the dispersion can be well maintained for a long time without aggregation and precipitation. Then, GO was transferred onto an O2 plasma-treated elastomer, here PET, substrate 104 with microstructured PDMS 106, as shown at 102, followed by blading for more uniform deposition and to remove excess GO contributing to a uniform GO layer 110, as shown at 108.
[0018] Nanographene (Gr) powder was first dispersed in N-methyl-2-pyrrolidone (NMP) solution (10 mg / ml) followed by ultrasonic treatment for 2 hours as shown at 112. The selection of the concentration of 10 mg / ml according to the preferred embodiment is described below. A settling process for 1 hour as shown at 113 was used after the ultrasonic treatment, which allowed the non-uniformly dispersed Gr to gravitationally disperse from the top layer, while the finely dispersed supernatant Gr nanoflakes were drop-cast onto the GO layer 110 as shown at 114 and dried in an oven at 80° C. for 30 minutes to form a uniform flexible conductive Gr coating 115. FIG. 10 shows an atomic force microscope image of the Gr coating 115 and the edge of the intermediate layer 110, showing a total height of about 600 nm according to the exemplary embodiment.
[0019] It should be noted that when using NMP as in the methods described above according to the exemplary embodiments, the substrate of the sensor preferably does not react with NMP, for example, PET film was used in the embodiments described herein, NMP can be substituted in other embodiments to extend the range of substrates.
[0020] Figure 2 shows SEM images of the as-prepared Gr-GO on polymer samples, (a)–(c) using the blading method described above for GO and top Gr, (d) using bottom Gr, (e) no GO layer present, (f) a thin layer of GO coated by the blading method described above, and (g) a thick layer of GO and buckles formed by drop casting of GO.
[0021] Specifically, Figures 2a-2c show scanning electron microscope images of the microstructure composite. According to the exemplary embodiment, there are several important factors that can affect the quality of the composite structure. First, if the bottom Gr is used for drop casting after precipitation, the coating is found to be uneven and very dense, covering all the microstructures responsible for the sensitivity and easily delaminating when pressed, as can be seen from the SEM image in Figure 2d. Second, if the GO layer is not present, the Gr nanoflakes are prone to agglomeration and the deposition is non-uniform, as seen in the SEM image in Figure 2e. According to the preferred embodiment, the thin GO layer, which serves as an interface layer between the polymer and Gr, is believed to provide a better affinity for Gr, mainly due to π-π interactions, and contribute to the formation of a Gr layer with better uniformity. It is also preferable to control the thickness of the GO layer. Figures 2f and 2g show the GO on PDMS samples prepared by braiding and drop casting, respectively. As can be seen from the scanning electron microscope images in Figures 2f and 2g, the GO layer coated by braiding according to the preferred embodiment was thin enough to maintain the surface morphology of the microstructured PDMS, while the drop-cast GO significantly altered the original microstructure, leaving voids and buckling at the side edges of the micropyramids. Therefore, it is preferable to use supernatant Gr and braid-coated GO to form high-quality Gr-GO layers on the PDMS microstructures.
[0022] Improving adhesion between GO and PDMS according to illustrative embodiments In embodiments that allow GO to interact with PDMS only through van der Waals forces, the films may separate if strong shear, bending, or adhesive forces are applied. To improve the adhesion between GO and PDMS, several methods can be implemented according to the preferred embodiment. One method may be to sputter a thin layer of copper onto PDMS, followed by GO deposition and annealing at 120 °C for 2 hours. This contributed to the formation of chemical bonds between copper and GO to enhance the adhesion strength. Another method focuses on electrostatic interactions. Since GO is negatively charged, a surface treatment can be performed on the PDMS surface to charge it positively. This strategy can generate a strong electrostatic force between GO and PDMS to greatly improve adhesion.
[0023] Material Variations for Pressure Sensitive Composites According to Various Embodiments It should be noted that the present invention is not limited to the materials used in the above embodiment.
[0024] In various embodiments, the present invention can also be applied to other low-dimensional electronic active material systems for flexible conductive coatings, such as, but not limited to, coatings made from other carbon allotropes, such as graphene, and other doped 2D materials, such as borophene, tungsten selenide, and silicene. These active 2D materials can be dispersed in a suitable dispersant and coated onto the surface of the elastomer microstructure using the same methods described above with reference to FIG. 1a. The conductive pathways formed on the elastomer surface can lead to a change in resistance when pressure is applied.
[0025] Other elastomeric materials can include, but are not limited to, other polymers such as (styrene-ethylene-butylene-styrene), silicone-based, and polyurethanes that offer a wide range of selective mechanical performance for various requirements.
[0026] Sensor Characterization According to Exemplary Embodiments Elastomers usually exhibit good deformability due to their low elastic modulus, which is advantageous for the design of pressure-sensitive elements. On the other hand, their performance is strongly affected by viscoelastic effects, such as hysteresis. However, sensors according to example embodiments can advantageously take advantage of the properties of the outer graphene layer to reduce the prohibitive viscoelastic effects and instead exhibit low hysteresis, weak temperature dependence, and weak strain rate dependence without sacrificing the sensing performance (e.g., high sensitivity, wide sensitivity range). Based on contact resistance change as the main sensing mechanism, the electrical performance of sensors according to example embodiments is highly dependent on the pressure response of the outer layer. Thus, viscosity-related issues can be compensated for by graphene coating according to example embodiments, which exhibits a more elastic property. Characterization of sensors according to example embodiments demonstrates reduced viscoelastic effects and is described below.
[0027] In the exemplary embodiment characterized below, each micropyramid has a base size of 50 μm and a height of 35.3 μm. The spacing between two pyramids is 50 μm. However, the invention is not limited to these dimensions.
[0028] The thickness of the graphene layer is 450 nm, and the thickness of the graphene oxide layer is 150 nm. It should be noted that the present invention is not limited to these thicknesses and materials.
[0029] For characterization, according to an exemplary embodiment, the composite material according to the exemplary embodiment was assembled as a graphene sensor 120 with designed interdigitated electrodes 116, 118 formed on the surface of the substrate (not shown) facing the coated microstructure 115. See Figures 1a-1c.
[0030] Specifically, the microstructure / sensor array 115 has a coated pyramidal tip 115 (compare FIG. 1a) over interdigitated electrodes 116, 118 (see FIGS. 1b and 1c), which in this embodiment faces downward and makes contact with the electrodes 116, 118. Commercially available biocompatible tape can be used to seal the sensor array over the electrodes 116, 118.
[0031] In an exemplary embodiment, the interdigitated electrodes 116, 118 were fabricated using standard lithography processes. Photoresist was coated on the substrate and exposed to UV light under a photomask. The photomask had an interdigitated electrode pattern, which was transferred to the photoresist after development. Titanium (Ti) and gold (Au) were then sputtered onto the photoresist. After lift-off, the excess photoresist and metal were washed away, leaving the interdigitated patterned metal on the substrate as the electrodes.
[0032] The designed interdigitated electrodes 116, 118, as shown diagrammatically in FIG. 1b, cover an area slightly larger than the sensor itself for a more robust performance according to the exemplary embodiment, discussed in the Theoretical Analysis section below. When compressive pressure (140 kPa) is applied to the sensor using a custom-built linear stage system with a strain rate of 5 μm / s, the resistance decreases by 10 6 From the order of Ω to 10 1 It changed to the order of Ω.
[0033] FIG. 3 shows graphs of resistance vs. pressure for graphene sensors according to example embodiments, where FIG. 3a corresponds to the front and back. The inset graph shows the sensitivity vs. pressure relationship. FIG. 3b shows the pressure response of graphene sensors according to various embodiments. FIG. 3c shows the effect of Gr concentration on the tunable pressure response according to example embodiments.
[0034] Specifically, FIG. 3a shows the resistance change corresponding to applied pressure according to the exemplary embodiment. Both loading and unloading results are shown. Only small electrical hysteresis was observed compared to previously reported piezoresistive sensors, indicating great potential for accurate sensing applications. This reduced hysteresis is due to the high elastic modulus of the graphene coating according to the exemplary embodiment, which advantageously imparts more elastic properties to the sensor.
[0035] The inset graph of FIG. 3a shows the relationship between pressure and sensitivity. The definition of sensitivity is S=δR / δP, which refers to the change in resistance within a very small change in pressure. The sensitivity of the graphene sensor according to the present invention is at least 10 6 Ω kPa -1 The sensitivity can be increased to 1000 MPa, indicating that it can detect small forces well. As the pressure increases, the sensitivity decreases as expected. Since the pressure-sensitivity curve can be achieved from the difference of the pressure-resistance curve through the definition of sensitivity, the smooth and consistent relationship of sensitivity vs. pressure indicates the stability of the sensor performance according to the exemplary embodiments. FIG. 3b shows the electrical pressure response of multiple graphene sensors according to the exemplary embodiments, shown as samples 1-7. The comparable results indicate the reliability of the fabrication method and the resulting sensors according to the exemplary embodiments. Furthermore, the Gr concentration used in the coating was found to be a significant factor affecting the pressure response of the sensor. According to the exemplary embodiments, the sensor performance can be adjusted by adjusting the concentration of Gr. As shown in FIG. 3c, according to various exemplary embodiments, "C10T1" (meaning a concentration of 10 mg / ml and single coating) shows the largest sensitivity range compared to "C5T1" and "C2T1" (meaning concentrations of 5 mg / ml and 2 mg / ml, respectively).
[0036] 4a shows a graph illustrating the strain rate independence of the graphene sensor according to an exemplary embodiment. The pressure response is the same at different strain rates. FIG. 4b shows a graph illustrating the temperature independence of the graphene sensor according to an exemplary embodiment. The pressure response shows little change when the temperature is increased from room temperature to 60° C.
[0037] For viscoelastic materials such as PDMS, the relationship between load and response is a function of frequency, since its viscous effects follow Newton's law. If pressure is applied at different strain rates, the corresponding response of PDMS is expected to be different. However, due to its flexibility and high elastic modulus, the graphene layer coated on the outside according to the exemplary embodiment can easily deform with the inner PDMS while exhibiting mainly elastic properties, which points to compliance with Hooke's law. According to the exemplary embodiment, the contact area between the electrode and the graphene layer is not visually affected by the vibration frequency, resulting in a strain rate independent resistance change of the sensor in response to the applied load. Figure 4a shows that the electrical response of the graphene sensor according to the exemplary embodiment is almost identical at different strain rates. As a result, the sensor according to the exemplary embodiment can operate reliably under load at various frequencies, which also indicates that the sensor according to the exemplary embodiment has great potential to detect vibrations. This will be explained in more detail below.
[0038] Regarding the effect of temperature, graphene has a much smaller thermal expansion coefficient compared to PDMS when the temperature increases, which can advantageously reduce the shift in sensor response induced by the geometric expansion of the sensor structure during temperature change. Meanwhile, the temperature coefficient of resistivity (TCR) of graphene is extremely small, which indicates that the resistivity of graphene is dominated by impurities and changes slowly with temperature. These two reasons contribute to the minimal temperature dependence of the graphene sensor according to the exemplary embodiment (see FIG. 4b) compared to previously reported studies. While the performance of existing sensors is highly dependent on temperature, the sensor according to the exemplary embodiment advantageously operates more reliably regardless of temperature changes, exhibiting stronger robustness in different working conditions.
[0039] FIG. 5 is a graph showing the reliability of the graphene sensor according to the exemplary embodiment when subjected to cyclic compression over an extended period of time, where FIG. 5a is the pressure response from cycle 1 to cycle 1,000,000; FIG. 5b is the loading and unloading response after 1,000,000 cycles, showing that the hysteresis remains low; FIG. 5c is a continuous measurement of the sensor performance over 1000 cycles; and FIG. 5d is the loading and unloading response of the graphene sensor according to the exemplary embodiment 8 weeks after fabrication, showing good reliability of the sensor according to the exemplary embodiment over several days.
[0040] Specifically, to characterize the reliability of the sensor during cyclic loading, the graphene sensor according to the exemplary embodiment was subjected to 1,000,000 cycles of cyclic pressure of 140 kPa. FIG. 5a shows the corresponding sensor performance from the 1st cycle to the 1,000,000th cycle. Both the sensitivity and the sensitivity range remained stable and consistent after 1,000,000 cycles. The almost comparable sensor response before and after 1,000,000 compressions indicates good reliability and compressibility of the graphene sensor. The slight shift in resistance observed especially during the first 100 cycles may be induced by more compact contact between the various graphene flakes of the coating layer. This situation is also shown in FIG. 5c, and the quantum tunneling phenomenon caused by these non-compact graphene flakes will be discussed later. The loading and unloading response of the graphene sensor according to the exemplary embodiment was plotted in FIG. 5b at the 1,000,000th compression. The low hysteresis is maintained even after countless cycles, indicating the reliable performance and high accuracy of the sensor according to the exemplary embodiment. Furthermore, good adhesion between Gr-GO and PDMS according to the exemplary embodiment is also revealed, and the outer layer will not be degraded or damaged after countless cycles due to its unique flexibility. Furthermore, FIG. 5c displays the continuous measurement results of the sensor response over the first 1000 cycles of compression. During the constant amplitude (140 kPa) loading, the maximum conductance of the sensor initially increased slightly due to the more compact stacking of graphene flakes. After that, it did not change and remained stable over the cycles. The characterization results illustrated good sensor reliability.
[0041] In previous studies investigating PEDOT:PSS coated microstructure sensors, the sensor performance deteriorated with time, resulting in low sensitivity. The reason for the deterioration is that the PSS moiety reacts with water, leading to degeneration. However, graphene is very inert and can advantageously act as a corrosion barrier against the diffusion of water and oxygen. In this case, the sensor coated with Gr-GO according to the exemplary embodiment can maintain its sensing capability even after a long period of time. Figure 5d shows the pressure response (both loading and unloading) of the graphene sensor according to the exemplary embodiment 8 weeks after fabrication. Good sensitivity, wide sensitivity range and low hysteresis are still shown without any degradation. This property is important for the use of the sensor according to the exemplary embodiment in applications such as wearable devices and health monitoring systems.
[0042] Interdigital Electrodes According to Exemplary Embodiments Figure 6 shows a schematic diagram illustrating a simulation of the equivalent surface resistance of a graphene sensor according to an exemplary embodiment, in which Figure 6a is an "electrode in sensor" design and Figure 6b is a "sensor in electrode" design. Figure 7a shows a schematic diagram of an equivalent circuit of a graphene sensor according to an exemplary embodiment.
[0043] The reason for utilizing interdigital electrodes according to the preferred embodiment is to increase the contact area between the sensor and the electrodes and reduce the effect of possible non-uniformly distributed coating defects. According to some exemplary embodiments, when a current passes through the surface of the micropyramids, each structure with Gr-GO coating can be considered as one resistor. The equivalent circuit of an array of micropyramids is a large number of resistors connected in series and parallel. The software TINA was utilized to model and analyze the resistance of this circuit (including the design of the electrodes) to achieve its equivalent resistance. When simulating the electrodes, several parameters were considered, such as the size, length, displacement, and position of the electrodes. It was found that the size of the electrodes is important. According to various exemplary embodiments, designs with different sizes can result in different characterization results of the sensor performance.
[0044] For the design of an "electrode in a sensor" which refers to a larger surface area than the electrode, the resistance of the sensor also plays a role in addition to other factors such as the length and position of the electrode, the dimensions of the sensor, etc. (See FIG. 6a.) In FIG. 6a, the slower surface area of the sensor is indicated by the length of the electrodes, e.g. 600, in the sensor resistor network 602 being shorter than the corresponding length 604 of the sensor resistor network 602.
[0045] However, for the "sensor-in-electrode" design, which refers to the case where the electrodes have a larger surface area than the sensor, it was found that only the misalignment and length of the electrodes predictably affect the resistance (see FIG. 6b). In FIG. 6b, the larger surface area of the electrodes is indicated by the length of the electrodes, e.g. 606, in the sensor resistor network 608 being the same as or larger than the length 610 of the sensor resistor network 608. The findings can make the circuit more robust during sensor characterization. Therefore, the latter design was chosen for the preferred embodiment. The resistance increased with increasing displacement of the two electrodes and decreased with increasing electrode length. This phenomenon can be further simplified to an equivalent circuit of "m×n" resistor network (see FIG. 7a), where m is proportional to the electrode length and n is proportional to the displacement.
[0046] Sensing Mechanism According to Exemplary Embodiments 7b-d show the IV curves of a graphene sensor according to an embodiment under different applied loads (0 kPa, 13.6 kPa, and 26.6 kPa, respectively). The non-linear relationship indicates quantum tunneling in the sensor according to an example embodiment.
[0047] Referring to FIG. 1b, when the Gr-GO / PDMS composite is assembled with electrodes to form a sensor 120 according to an exemplary embodiment, a pair of interdigitated electrodes 116, 118 is used for testing. The interdigitated electrodes 116, 118 consist of two interlocking comb-shaped arrays of metal, and the electrodes 116, 118 are disposed adjacent to each other on the same surface of the substrate. Current flows from one electrode 116, passes through the Gr-GO coating on the surface of the microstructures, e.g., micropyramids, and then flows to the other electrode 118. The total resistance of the sensor according to the embodiment is the electrode resistance (R e ), contact resistance (R c ), and the surface resistance of the Gr layer (R s ) is contributed by three parts: R e does not change with pressure. R c changes significantly with pressure, mainly due to the change in contact area and also due to quantum tunneling from the stacked graphene flakes. R s changes slightly with pressure due to the change in surface area during compression, but this change is c is small compared to the change in
[0048] The simplified circuit is shown in Figure 7a, where R s is considered as a collection of resistor networks with nearly constant resistance. R cis a collection of micro-structures, here micro-pyramids, in contact with an electrode and having a pressure-induced resistance change. Each micro-pyramid is considered to have the same resistance and the same resistance change during loading. The number k is also related to the area of the electrode and the density of the micro-pyramids. Figures 7b-7d show the I-V curve section of a graphene sensor according to an embodiment under different applied loads (0 kPa, 13.6 kPa, and 26.6 kPa, respectively). The resistance decreases with increasing applied voltage, indicating the quantum tunneling effect present in the graphene sensor according to the exemplary embodiment. The tunneling effect arises from the nanoscale gaps between the graphene flakes. Since the distance of each gap decreases with increasing pressure, the tunneling effect will be attenuated during compression at higher pressures. This is shown in Figures 7b-7d through the reduced nonlinearity of the I-V relationship observed as the pressure increases.
[0049] Sensor Demonstration According to Exemplary Embodiments 8a and 8b are diagrams illustrating the continuous detection of small weights by a sensor according to an exemplary embodiment. Specifically, since the graphene sensor according to the present embodiment can detect tactile pressure sensitively and stably, an experiment of continuous detection of small weights was conducted. A sensor having a dimension of 6 mm×6 mm according to an exemplary embodiment was fabricated to detect small weights of 100 mg, 50 mg, and 30 mg. The minimum pressure was equivalent to about 8 Pa. As shown in FIG. 8a, the sensor according to the exemplary embodiment can continuously detect these small weights with good stability for a duration of about 3 seconds. As shown in FIG. 8b, the sensor according to the exemplary embodiment can output consistent resistance changes for the same small, which indicates its good ability to continuously detect ultra-small tactile signals. From previous studies, touch receptors on human fingertips can detect pressures in the approximate range of 100 Pa to 100 kPa. Compared with such requirements, the sensor according to the exemplary embodiment has good potential to be utilized in electronic skin, and in one exemplary embodiment, it shows a detection range of 8 Pa to 140 kPa.
[0050] In addition to a large sensing range, a high time resolution is also desired for tactile sensors, which refers to the ability to distinguish high-frequency signals, such as vibrations. In essence, the protein fibers spun by spiders exhibit a unique combination of high tensile strength and good extensibility. These spider silk-based network structures contribute to the excellent vibration detection capabilities of spider webs. In the case of sensors according to exemplary embodiments, graphene also has a very high elastic modulus and at the same time has a certain flexibility, similar to spider webs in terms of both structure and properties. Due to these similarities, a fast time response is advantageously exhibited by graphene sensors according to exemplary embodiments, providing the ability to detect high frequencies. In this way, sensors according to exemplary embodiments can recognize a large time resolution for the tactile pressure that can be applied to detect vibrations.
[0051] FIG. 9a shows a schematic diagram of a setup for detecting vibrations using a graphene sensor according to an exemplary embodiment. Acoustic waves were used to generate high frequency dynamic forces. FIG. 9b shows a graph illustrating the detection results of dynamic forces with frequencies of 500 Hz, 1000 Hz, and 1500 Hz. FIG. 9c-9e show the Fast Fourier Transform (FFT) of each detection result in FIG. 9b, showing the corresponding frequencies 901-903 detected by the sensor.
[0052] Referring to FIG. 9a, a speaker 910 was utilized to generate sound waves with custom adjustable frequencies to provide high frequency signals in the experimental setup. According to an exemplary embodiment, sound waves were applied perpendicularly onto the surface of the sensor 912 to induce a dynamic external force. When the sensor 912 receives the dynamic force, it will be quickly compressed and released to give a corresponding dynamic electrical response. The graphene sensor 912 according to an exemplary embodiment has a frequency-independent pressure response, so different frequencies do not affect the amplitude of the sensor response. This characteristic is beneficial for vibration detection and accurate recognition of frequency without introducing other factors. It is shown that the sensor 912 according to an embodiment can detect vibrations with a high frequency of at least 1500 Hz, and FIG. 9b gives the detection results of vibrations with frequencies of 500 Hz, 1000 Hz, and 1500 Hz. Using a Fast Fourier Transform (FFT) algorithm, the frequency of the vibration can be recognized by analyzing the electrical response through the sensor output. Figures 9c to 9e show the FFT analysis of these signals (500 Hz, 1000 Hz, and 1500 Hz, respectively).
[0053] In an exemplary embodiment, a composite structure for a pressure sensor is provided, the composite structure including an array of microstructures fabricated from an elastomeric material and a flexible conductive coating formed on the array of microstructures such that a surface morphology of the array of microstructures is substantially maintained for the coated array of microstructures, the conductive coating exhibiting a Young's modulus higher than that of the elastomeric material.
[0054] The Young's modulus may be about an order of magnitude higher than that of the elastomeric material, or even more.
[0055] The flexible conductive coating may comprise a low dimensional electro-active material system, which may exhibit electron tunneling properties.
[0056] The low dimensional electronically active material system comprises a homogeneous layer.
[0057] The low dimensional electro-active material system may include a 2D material structure, which may include a nanoflake.
[0058] The composite structure can further include a substrate for the array of microstructures.
[0059] The composite structure may further include an intermediate layer between the array of microstructures and the flexible conductive coating to improve the uniformity of the flexible conductive coating.
[0060] In an exemplary embodiment, a pressure sensor is provided that includes the composite structure of the above embodiment.
[0061] The pressure sensor can exhibit reduced hysteresis based on the elastic properties of the composite structure compared to the viscoelastic properties of the elastomeric material of the array of microstructures.
[0062] The pressure sensor can exhibit a substantially frequency independent pressure response.
[0063] The pressure sensor can exhibit a pressure response that is substantially independent of temperature.
[0064] The pressure sensor can exhibit a pressure response that is substantially independent of humidity.
[0065] The pressure sensor may further include an electrode disposed on the coated array of microstructures to measure a resistance of an electrical path that includes a site on the surface of the coated array of microstructures. The electrode may include two interdigitated electrodes.
[0066] The resistance may change as a result of compression of the coated array of microstructures under pressure: the resistance may decrease as the pressure increases.
[0067] 11 shows a flowchart 1100 illustrating a method of manufacturing a composite structure for a pressure sensor according to an example embodiment. In step 1102, an array of microstructures made from an elastomeric material is formed. In step 1104, a flexible conductive coating is formed on the array of microstructures such that the surface morphology of the microstructures is substantially maintained for the coated array of microstructures, the conductive coating exhibiting a Young's modulus higher than that of the elastomeric material.
[0068] Forming the flexible covering can include drop casting a first material onto the array of microstructures.
[0069] The method can include blade a second material onto the array of microstructures prior to drop casting the first material.
[0070] The first material can include a low dimensional electronically active material system.
[0071] Low-dimensional electronically active material systems can exhibit electron tunneling properties.
[0072] The low dimensional electronically active material system can include a homogeneous layer.
[0073] The electroactive material system may include a 2D material structure. The 2D material structure may include nanoflakes.
[0074] The method may further include disposing electrodes on the coated array of microstructures to measure the resistance of an electrical path that includes a site on the surface of the coated array of microstructures.
[0075] In an exemplary embodiment, a method of pressure sensing using the presser sensor of the above-described embodiments is provided.
[0076] Embodiments of the invention may have one or more of the following features and associated benefits / advantages:
[0077] [Table 1]
[0078] Embodiments of the present invention may have the following applications, by way of example and not limitation: - High sensitivity pressure sensor for long term detection of pulse and other health monitoring applications - Electronic skin for detecting both pressure and vibration.
[0079] Aspects of the systems and methods described herein, such as signal processing of electrical signals, may be implemented as functions programmed into any of the programmable logic devices (PLDs), such as field programmable gate arrays (FPGAs), programmable array logic (PAL) devices, electrically programmable logic and memory devices, and standard cell-based devices, as well as application specific integrated circuits (ASICs). Other possibilities for implementing aspects of the systems include microcontrollers with memory (such as electronically erasable programmable read-only memory (EEPROM)), embedded microprocessors, firmware, software, etc. Additionally, aspects of the systems may be embodied in microprocessors with software-based circuit emulation, discrete logic (sequential and combinatorial), custom devices, fuzzy (neural) logic, quantum devices, and hybrids of any of the above device types. Of course, the underlying device technology can be provided in a variety of component types, e.g., complementary metal oxide semiconductor field effect transistor (MOSFET) technology, bipolar technologies such as emitter coupled logic (ECL), polymer technologies (e.g., silicon-conjugated polymer and metal-conjugated polymer-metal structures), mixed analog and digital, etc.
[0080] The above description of illustrated embodiments of the systems and methods is not intended to be exhaustive or to limit the systems and methods to the precise forms disclosed. While specific and exemplary embodiments of the system components and methods have been described herein for illustrative purposes, those skilled in the art will recognize that various equivalent modifications are possible within the scope of the systems, components and methods. The teachings of the systems and methods provided herein may be applied to other processing systems and methods, as well as the systems and methods described above.
[0081] The elements and acts of the various embodiments described above can be combined to provide further embodiments. These and other changes can be made to the systems and methods in light of the above detailed description.
[0082] In general, in the following claims, the terms used should not be construed to limit the systems and methods to the specific embodiments disclosed in the specification and claims, but should be construed to include all processing systems that operate in accordance with the claims. Thus, the systems and methods are not limited by this disclosure; instead, the scope of the systems and methods should be determined entirely by the claims.
[0083] Unless the context clearly requires otherwise, throughout the specification and claims, words like "comprises," "comprises," and the like are to be construed in an inclusive sense, rather than an exclusive or exhaustive sense, i.e., words using the singular or plural in the sense of "including but not limited to" include the plural or singular, respectively. Additionally, the terms "herein," "herein," "above," "below," and words of similar import refer to this application as a whole and not to any particular portion of this application. When the word "or" is used in connection with a list of two or more items, the word includes all of the following interpretations of the word: any of the items in the list, all of the items in the list, and any combination of the items in the list.
Claims
1. 1. A composite structure for a pressure sensor, comprising: an array of microstructures made from an elastomeric material; a flexible conductive coating formed on the array of microstructures such that the surface morphology of the array of microstructures is substantially maintained for the array of microstructures coated thereon; Equipped with the flexible conductive coating exhibits a Young's modulus greater than a Young's modulus of the elastomeric material; The composite structure further comprises a plurality of electrodes disposed on the array of coated microstructures; The plurality of electrodes are configured to measure a change in contact resistance between the flexible conductive coating and the plurality of electrodes as a result of pressure on the composite structure. the flexible conductive coating comprises a low dimensional electronically active material system; The low-dimensional electronically active material system exhibits electron tunneling properties. A composite structure comprising:
2. 10. The composite structure of claim 1, wherein the Young's modulus of the flexible conductive coating is approximately one order of magnitude or more higher than the Young's modulus of the elastomeric material.
3. 3. The composite structure of claim 1 or 2, wherein the low dimensional electronically active material system comprises a homogeneous layer.
4. 4. The composite structure of claim 1, wherein the low dimensional electro-active material system comprises a 2D material structure.
5. The composite structure of claim 4 , wherein the 2D material structures comprise nanoflakes.
6. 6. The composite structure of claim 1, further comprising a substrate for said microstructure.
7. 7. The composite structure of claim 1, further comprising an intermediate layer between the array of microstructures and the flexible conductive coating to improve uniformity of the flexible conductive coating.
8. A pressure sensor comprising the composite structure according to any one of claims 1 to 7.
9. 10. The pressure sensor of claim 8, wherein the flexible conductive coating exhibits a higher Young's modulus than the elastomeric material of the array of microstructures, thereby exhibiting reduced hysteresis.
10. 10. A pressure sensor according to claim 8 or 9, characterized in that it exhibits a substantially frequency independent pressure response.
11. 11. A pressure sensor according to any one of claims 8 to 10, characterized in that it exhibits a pressure response that is substantially independent of temperature.
12. 12. A pressure sensor according to any one of claims 8 to 11, characterized in that it exhibits a pressure response that is substantially independent of humidity.
13. A pressure sensor as described in any one of claims 8 to 12, characterized in that the multiple electrodes are positioned on the opposite side of the flexible conductive coating compared to the array of microstructures.
14. The pressure sensor of claim 13 , wherein the plurality of electrodes includes two interdigitated electrodes.
15. 15. The pressure sensor of claim 13 or 14, wherein the resistance changes as a result of compression of the array of coated microstructures under pressure.
16. 16. The pressure sensor of claim 15, wherein the resistance decreases with increasing pressure.
17. 1. A method of manufacturing a composite structure for a pressure sensor, comprising: forming an array of microstructures made from an elastomeric material; forming a flexible conductive coating formed on the array of microstructures such that a surface morphology of the array of microstructures is substantially maintained for the array of microstructures coated thereon; Including, the flexible conductive coating exhibits a Young's modulus greater than a Young's modulus of the elastomeric material; The method further includes disposing a plurality of electrodes on the array of coated microstructures; The plurality of electrodes are configured to measure a change in contact resistance between the flexible conductive coating and the plurality of electrodes as a result of pressure on the composite structure. the flexible conductive coating comprises a low dimensional electronically active material system; The low-dimensional electronically active material system exhibits electron tunneling properties. A method comprising:
18. 20. The method of claim 17, wherein forming the flexible conductive coating comprises drop casting a first material onto the array of microstructures.
19. 20. The method of claim 18, comprising blade a second material onto the array of microstructures prior to drop casting the first material.
20. 20. The method of any one of claims 17 to 19, wherein the low-dimensional electronically active material system comprises a homogeneous layer.
21. 21. The method of any one of claims 17 to 20, wherein the low-dimensional electro-active material system comprises a 2D material structure.
22. 22. The method of claim 21 , wherein the 2D material structures comprise nanoflakes.
23. 23. The method of any one of claims 17 to 22, further comprising disposing a plurality of electrodes on the composite structure to measure the resistance of an electrical path that includes a portion of a surface of the array of coated microstructures.
Citation Information
Patent Citations
Conductive Geotextile
JP2019506542A
Conductive roller and process for producing the same
WO2008143012A1
Enhanced pressure sensing performance for pressure sensors
WO2018144772A1
A method and system for forming a multilayer composite structure
WO2019043499A1